MicroCT imaging of long bones: archaeozoology and domestication from a digital perspective - Boschin, Francesco; Bernardini, Federico (Proceedings of the 2022 IMEKO TC4 International Conference on Metrology for Archaeology and Cultural Heritage, 2023)
X-ray microCT imaging offers the possibility to study interior structure of animal remains detecting agerelated changes of bone microstructure. In the present paper we analyse patterns in the development of diaphyseal structure in canids. In particular, the first metacarpal of present-day and archaeological red fox (Vulpes vulpes) and wolf (Canis lupus) individuals have been analysed. Variables describing bone structure were measured by inferring bone development through observation of cross-sections. Results show how bone structure changes through life and how this approach allows to separate young individuals from older ones. This is important both from a zooarchaeological perspective, since microCT imaging is a non-invasive tool to estimate the age at death of animal remains, and to discriminate taxa characterized by a close morphology but different adult body size.